(untitled) - Ward, David (New York, 2008)
After tasting freedom, the former slaves are soon back under the control of the menacing Spears, and this time Corki and Pippa are separated as Corki, in training to be a Spear, seeks a way to work within the system to gain freedom for himself and his friends.
Keywords: Slavery,Torture,Science fiction,Tra tấn,Khoa học viễn tưởng,Chế độ nô lệ; Fiction,Fiction,Viễn tưởng